Gender in history - Wiesner, Merry E. 1952- (Blackwell, 2001)
Over the past 20 years, the study of history has been revolutionized by considerations of gender, and yet most books on the subject focus on only one period or region. This concise overview redresses the balance, exploring the construction of gender in many cultures around the world at different times. The material is presented thematically, encouraging readers to appreciate the connections between gender and other structures such as the family, the economy, law, religion, sexuality and the state. The author investigates how what it meant to be a man or woman was shaped by these institutions, and how they in turn were influenced by gender. Within each chapter, information is arranged chronologically in order to highlight the ways in which gender structures have varied over time.
Keywords: Histoire sociale; Rôle selon le sexe - Histoire; Sekseverschillen; Sociale geschiedenis; Geschichte; Geschlechtsunterschied; Sozialgeschichte; Sex role -- History; Social history; Geschlechterrolle